A blockchain-driven business model for supplier selection and order allocation leveraging smart contracts in supply chains - Emami, Ashkan; Seifbarghy, Mehdi; Abbas, Antragama Ewa; Chattinnawat, Wichai; Aydin, Nezir (ELSEVIER, 2025)
Supply chain operations have tended to become more complex, thus placing significant pressure on one of the most critical processes: supplier selection and order allocation (SSOA). This process involves a focal company selecting suppliers and allocating orders to obtain required materials. Achieving effective SSOA processes is challenged by (1) reliance on centralized governance and (2) ensuring effective contract management. While so called smart contracts could address these challenges, design knowledge about such technology - particularly in the SSOA context - is underexplored in the literature. In this paper we design a smart contract for SSOA in supply chains. We conducted a design science research study and developed three core artifacts: (1) a mathematical description of SSOA; (2) a system model of actor interactions; and (3) SSOA-relevant algorithms. Utilizing the Ethereum blockchain, we demonstrated and tested our smart contracts through scenario analysis. We found that our design is feasible and highly likely to address centralization and effectiveness challenges in SSOA. This paper contributes to the literature by demonstrating how smart contract design focusing on SSOA can further enhance blockchain-driven business models. In addition, we offer prescriptive knowledge on developing smart contracts for SSOA in supply chains.
Keywords: Supply chain management; Supplier selection; Order allocation; Blockchain applications; Smart contract; MULTI-STAKEHOLDER; DUAL-CHANNEL; COORDINATION; OPTIMIZATION; TECHNOLOGIES; OPERATIONS; LOGISTICS; SYSTEM; IMPACT; Business & Economics